Primary Focal Segmental Glomerulosclerosis - Apiyangkool, Tanin; Satirapoj, Bancha (Journal of the Nephrology Society of Thailand, 2023)
Primary focal segmental glomerulosclerosis (FSGS) has become increasing prevalent in the recent years, and it is one of the important causes of chronic kidney disease. The presentation may range from asymptomatic proteinuria to full-blown nephrotic syndrome. To make a correct diagnosis, kidney biopsy is mandatory. An autoimmune process is believed to be involved in the pathogenesis of primary FSGS, but the mechanisms remain poorly understood. The treatment includes symptomatic management to reduce proteinuria and blood pressure and immunosuppressive therapy. Glucocorticoid is the first line treatment with calcineurin inhibitor as an alternative therapy. The goal is to reduce proteinuria, lower blood pressure and preserve kidney function.